Lenticulostriatal ischemia shows relevant SSTR expression on PET/CT imaging using the novel SSTR-targeting peptide 18F-SiTATE: interesting images - Kunte, Sophie Carina; Unterrainer, Lena M.; Kunz, Wolfgang G.; Winkelmann, Michael; Lindner, Simon; Jurkschat, Klaus; Wängler, Carmen; Wängler, Björn; Schirrmacher, Ralf; Bartenstein, Peter; Belka, Claus; Schichor, Christian; et al. (Clinical nuclear medicine, 2024)
A 64-year-old woman with meningioma presented with left-sided lenticulostriatal ischemia following craniotomy and debulking of a sphenoid wing meningioma. For subsequent radiotherapy planning, an SSTR-targeted PET/CT using the novel ligand 18F-SiTATE was performed 2.5 months thereafter. The meningioma remnants showed transosseous, intrasellar, and perivascular extension around the internal carotid artery with strong SSTR expression. Moreover, there was focal 18F-SiTATE uptake in the left caudate and corresponding contrast enhancement due to postischemic blood-brain barrier disruption and reactive SSTR expression. Therefore, increased cortical or subcortical SSTR PET signal may be related to ischemic changes even in the subacute stage after initial stroke.